2020
DOI: 10.1177/0300060520943792
|View full text |Cite
|
Sign up to set email alerts
|

MiR-28-5p mediates the anti-proliferative and pro-apoptotic effects of curcumin on human diffuse large B-cell lymphoma cells

Abstract: Objective To investigate the anti-proliferative and pro-apoptotic effects of curcumin on diffuse large B-cell lymphoma (DLBCL) cells and explore the mechanism. Methods OCI-LY7 cells were treated with curcumin (2.5, 5, 10, 20, and 40 μM) for 24, 48, or 72 hours. Cell viability and apoptosis were determined using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5 diphenyl tetrazolium bromide assay and TdT-mediated dUTP nick-end labeling staining, respectively. MiR-28-5p expression was detected via qRT-PCR. The binding site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Additionally, miR-28-5p inhibited cell proliferation and migration in Renal Cell Carcinoma by directly inhibiting the Rap1b gene [ 41 ]. The miR-28-5p was also reported to inhibit cell growth and promote apoptosis of DLBCL cells through Curcumin [ 42 ]. Studies have also found that miR-28-5p was upregulated in some tumors, implying their critical role in tumor metastasis and invasion [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-28-5p inhibited cell proliferation and migration in Renal Cell Carcinoma by directly inhibiting the Rap1b gene [ 41 ]. The miR-28-5p was also reported to inhibit cell growth and promote apoptosis of DLBCL cells through Curcumin [ 42 ]. Studies have also found that miR-28-5p was upregulated in some tumors, implying their critical role in tumor metastasis and invasion [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…By increasing miRNA-28–5p expression, curcumin reduces BECN1 expression and enhances p62 expression. 96 Curcumin-mediated lncRNA regulation has been also reported. Briefly, lncRNAs are similar to miRNAs in terms of inability in encoding proteins and both of them have regulatory functions in cells.…”
Section: Curcumin and Lymphomamentioning
confidence: 98%
“… 95 Curcumin suppresses progression and survival of lymphoma cells. 96 miRNA-28–5p is another factor involved in regulating progression of lymphoma. miRNA-28–5p has poor expression in lymphoma and its upregulation suppresses tumor progression via YWHAZ down-regulation.…”
Section: Curcumin and Lymphomamentioning
confidence: 99%
“…A detailed investigation of ferroptosis responses for these natural products and miRNAs is warranted. Curcumin [272] miR-125b-5p PEITC [273], quercetin [274], EGCG [275], berberine [276] miR-1287-5p Curcumin [277] miR-129-5p Matrine [278] miR-142-3p Artesunate [279], quercetin [280], curcumin [281] miR-143-3p Curcumin [282], EGCG [283,284], sulforaphane [285], quercetin [286] miR-144-3p Curcumin [287] miR-15a-5p Curcumin [288], baicalin [289], Withaferin A [290] miR-15a-3p EGCG [284] miR-205-5p Cryptotanshinone ↓ [291] proanthocyanidins ↓ [292], curcumin [293] miR-214-3p EGCG [284], sulforaphane [285] miR-25-3p Withaferin A [294] miR-27a-3p β-elemene [295], quercetin [296] miR-28-5p Curcumin [297] miR-302a-3p Curcumin [298] miR-324-3p Salinomycin ↓ [299] miR-365a-3p Sulforaphane [300] miR-375-3p Solasonine [301] miR-409-3p Curcumin [302] miR-429 Curcumin [303], berberine ↓ [304,305] miR-489-3p Curcumin [306] Ferroptosisinhibiting miRNAs miR-18a-5p Curcumin ↓ [307] miR-19a-3p Berberine [308], proanthocyanidins …”
Section: Ferroptosis-modulating Mirnas Are Associated With Some Natur...mentioning
confidence: 99%
“…Ferroptosis-inducing natural products, such as curcumin, sulforaphane, and solasonine, are associated with upregulating ferroptosis-inducing miRNAs ( Table 4 ). Curcumin induces the antiproliferation and apoptosis of large B-cell lymphoma cells by upregulating miR-28-5p, which is reversed by miR-28-5p inhibition [ 297 ]. Similarly, curcumin inhibits the proliferation and EMT gene expression of colon cancer cells by inducing miR-302a-3p expression [ 298 ].…”
Section: Ferroptosis-modulating Mirnas Are Associated With Some Natur...mentioning
confidence: 99%